PENGARUH KINERJA LINGKUNGAN, BIAYA LINGKUNGAN, DAN CORPORATE SOCIAL RESPONSIBILITY PADA KINERJA KEUANGAN - Asriyanti Kaat; Sofian Sofian (Universitas Katolik Widya Mandala Surabaya, 2023)
This study aims to analyze and empirically test the effect of environmental performance, environmental costs, and corporate social responsibility on the financial performance of mining sector companies listed on the Indonesia Stock Exchange. The design of this study uses quantitative research with hypothesis testing. The type of data used is quantitative data using secondary data sources obtained from the financial statements and annual reports of mining companies for the 2018-2021 period listed on the Indonesia Stock Exchange. The research data is in the form of panel data and the object of this study is a mining company listed on the Indonesia Stock Exchange and listed in PROPER in 2018-2021 with the data collection method used is the documentation method. The sample used in this study was 25 companies. The data analysis technique used is multiple linear analysis using the SPSS version 23 program. The results showed that environmental performance does not affect financial performance, environmental costs negatively affect financial performance., and corporate social responsibility (CSR) does not affect financial performance.